2009
DOI: 10.1007/s11596-009-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of ascorbic acid and thiamine supplementation against damage caused by lead in the testes of mice

Abstract: Lead is a ubiquitous environmental and industrial pollutant that may have toxic effects on the male. Vitamins may protect against toxic effects of lead in the liver and reproductive system, which is confirmed by our initial research. The aim of this study was to further investigate the protective effects of vitamins (ascorbic acid combined with thiamine) on lead acetate (Pb)-induced reproductive toxicities in mice and study the possible mechanisms underlying these effects. Forty-five male mice were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…This caused increased interstitial space and consequently tissue edema [30]. Damaged DNA or increased apoptosis in germinal cells of seminiferous tubules are thought to be one of the effect mechanisms of lead [34,39]. Another mechanism is suppression of hypothalamicpituitary-testicular axis [9].…”
Section: Discussionmentioning
confidence: 99%
“…This caused increased interstitial space and consequently tissue edema [30]. Damaged DNA or increased apoptosis in germinal cells of seminiferous tubules are thought to be one of the effect mechanisms of lead [34,39]. Another mechanism is suppression of hypothalamicpituitary-testicular axis [9].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of risk element uptake on body weight and weight gain of rats was investigated by Paul et al (2002) in the case of arsenic, Asagba (2010) in the case of cadmium, Smith et al (2008) and Shan et al (2009) and in the case of lead. Whereas animal exposure to arsenic and lead did not result in the animal growth suppression regardless of element rate and experiment duration, suppressed animal growth was observed after dietary cadmium exposure of rats.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that introduction of ascorbic acid during pregnancy and lactation caused to some extent amelioration of oxidative stress in the developing hippocampus. Shan et al (2009) examined the defensive effects of ascorbic acid and thiamine against the toxic effects of lead on testes of mice. Exposure to lead exhibited a significant decrease in epididymal sperm count and motility, along with the induction of apoptosis through activation of caspase-3, Fas/Fas-L and Bcl-2.…”
Section: Vitaminsmentioning
confidence: 99%